L’interculturel comme horizon pour l’éducation : le cas de l’école primaire en République d’Irlande - Patricia Fournier-Noël (Revue LISA)
The intercultural horizon is a newcomer in the educational landscape of the Republic of Ireland. Its integration into the other horizons of the education system, namely the denominational and the national horizons, raises the question of the compatibility of these different horizons. Our analysis focuses on primary education and is based on a multiple-case study carried out in four Irish denominational primary schools the purpose of which is to see to what extent the practice observed is compatible with the new intercultural horizon, particularly as regards two of its dimensions, i.e. the celebration of diversity and anti-racism.